Strategi Komunikasi Efektif Guru Dalam Menunjang Keberhasilan Electronic Learning - Maratush Sholikhah; niken ristianah (Intizam, Jurnal Manajemen Pendidikan Islam, 2022)
The COVID-19 pandemic has changed almost all lines of life in the affected communities, including education. The government's efforts to protect citizens from the spread of COVID-19, learning activities are carried out from home. Therefore, the teacher as the main role in the delivery of learning must be able to make a strategy so that the lesson reaches the students. In running the e-learning program, teachers must be able to build good and effective communication to all members who play a role in the implementation of the electronic learning program.The teacher's effective communication strategy is to optimize the teacher's skills in managing learning effectively and efficiently, preparing interesting learning materials and methods, ensuring students' readiness to accept learning, utilizing learning support media and evaluation related to feedback from students after receiving the material. The e-learning program has an impact on changing the learning culture that refers to the concept of student self-learning, so teachers and students can take advantage of digital platforms that provide communication support applications to carry out learning with guaranteed access whenever and wherever teachers and students are.